The Effectiveness of Cognitive Rehabilitation Training on Prospective Memory and Cognitive Flexibility in Individuals with Depression - Pourjaberi, Behnaz; Shirkavand, Naser; Ashoori, Jamal (International Journal of Education and Cognitive Sciences, 2022)
Individuals with depression often face significant challenges in memory and cognitive flexibility. Therefore, the aim of this study was to determine the effectiveness of cognitive rehabilitation training on prospective memory and cognitive flexibility in individuals with depression. This quasi-experimental study employed a pre-test and post-test design with both experimental and control groups. The research population consisted of individuals with depression seeking treatment at counseling centers in Ahvaz during the summer of 2023, from which 30 were conveniently sampled and randomly assigned to two equal groups. The experimental group underwent 10 one-hour sessions of cognitive rehabilitation training, while the control group received no intervention during this period. Data were collected using the Prospective Memory Subscale and the Cognitive Flexibility Inventory and analyzed using Chi-square and Multivariate Analysis of Covariance (MANCOVA) in SPSS-24. The findings indicated that there were significant differences between the experimental and control groups in both prospective memory and cognitive flexibility. In other words, cognitive rehabilitation training improved both prospective memory and cognitive flexibility in individuals with depression (P < 0.001). Considering the effectiveness of cognitive rehabilitation training in improving prospective memory and cognitive flexibility in individuals with depression, planning to incorporate cognitive rehabilitation training alongside other educational methods is effective in enhancing these characteristics.